Geomagnetic induced current modelling and analysis on high voltage power system - Khurshid Z.M.; Ab Aziz N.F.; Ab Kadir M.Z.A.; Rhazali Z.A. (IOP Publishing Ltd, 2023)
Computer aided analysis; Computer aided software engineering; Electric fields; Electric grounding; Electric losses; Electric power transmission networks; Electric windings; Geomagnetism; Harmonic analysis; Intercalation; Power transformers; Reactive power; Software testing; Even and odd harmonics; Geomagnetic disturbance; Geomagnetic induced currents; Geomagnetically induced currents; High-voltage power systems; Induced electric fields; Modelling and analysis; Power system simulators; Electric load loss